(untitled) (Research, Society and Development, 2020)
The present study seeks to analyze and highlight the importance of playfulness in the construction of teaching-learning in education, verifying the different ways of using this type of education methodology. This study is an integrative review research, using search indexes in the electronic databases and portals Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (LILACS) and PubMed. The data were analyzed using tables and discussed with the current and pertinent literature. Seven articles were identified, being in qualitative, descriptive, and experimental approaches. After analysis, it was noted that part of the publications were related to the year 2019 (35.4%), the majority being published in periodicals in Brazil. In addition, it became noticeable that, among the articles included, there are several areas of health, such as, for example, psychology, nursing, medicine, dentistry, especially those of social sciences and engineering. Through the review directed to the relevance of using playful methodologies in the transfer of knowledge, it was identified that these strategies help and enhance learning in health education. Thus, it provides numerous benefits for teachers and students, corroborating for a comprehensive training.